TikTok Social Media Literacy in Verifying the Dissemination of Hoax News among University Students - Dewi, Paradia Kristanti; Azhar, Anang Anas (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The ability to exercise media literacy is essential for filtering digital information, preventing the spread of hoaxes, and protecting the public from disinformation in the era of social media. This study explores how Islamic Communication and Broadcasting Program students, Faculty of Da'wah and Communication, Universitas Islam Negeri Sumatera Utara (class of 2021) apply media literacy in filtering information from the TikTok platform. This research employs a qualitative descriptive method, with five students as subjects, utilising interviews, observation, and data analysis based on the framework of Huberman and Miles. The findings indicate that students demonstrate varying levels of media literacy when verifying information on TikTok. While some can critically evaluate and filter content, many still consume and accept information without verification. TikTok's algorithm prioritises viral content and accelerates the spread of hoaxes, especially when the content is visually engaging. The lack of digital literacy education, social influence, and limited training in information verification further exacerbate the issue. Students tend to verify information only when it is perceived as personally relevant. Therefore, enhancing media literacy is crucial to enable students to be more critical, selective, and responsible in accessing and disseminating information. Conclusion: The students' media literacy level is moderate, playing a role in evaluating, producing content, and verifying information on social media.